Selenium Status and Oxidative Stress in SARS-CoV-2 Patients - Andrejs Šķesters; Anna Lece; Dmitrijs Kustovs; Maksims Zolovs (Medicina, 2023)
Background and Objectives: Insufficient intake of essential micronutrient selenium (Se) increases the susceptibility to diseases associated with oxidative stress. The study aim was to assess Se status and oxidative stress in COVID-19 patients depending on severity of the disease. Materials and Methods: Blood plasma of 80 post-COVID-19 disease patients and 40 acutely ill patients were investigated. Concentration of Se was detected by a fluorometric method with di-amino-naphthalene using acidic hydrolysis. Selenoprotein P (Sepp1), malondialdehyde (MDA), and 4-hydroxynonenal (4-HNE) and their metabolite adducts were evaluated by spectrophotometric methods using commercial assay kits. Results: Obtained results demonstrated that Se and Sepp1 concentration in acute patients were significantly (p < 0.05 for Se and p < 0.001 for Sepp1) decreased compared with post-COVID-19 disease patients. However, in post-COVID-19 disease patients, Se values were close to the low limit of the norm for the European population. 4-HNE adducts concentration as a marker of lipid peroxidation was significantly increased in the acute patients group compared to the recovery group (p < 0.001). Conclusions: COVID-19 pathology is characterized by the induction of oxidative stress and suppression of antioxidant defenses during the acute phase. Lower levels of Se and Sepp1 and higher levels of reactive oxygen species reflect this imbalance, highlighting the role of oxidative stress in the disease’s pathogenesis.